Results of research by Ukrainian scientists in Elbrus highlands of factors on health and longevity - Білошицький, П.В.; Ключко, О.М.; Онопчук, Ю.М. (Proceedings of National Aviation University (archive), 2008)
Results of many year investigations of high mountain factors that influence on health and life duration are suggested. Experimental data, results of mathematic simulation of ischemic heart disease linked with hypoxia problems studying and information concerning invented methods of medical treatment are given.